Posthospital home visit as teaching tool for internal medicine residents. Issue 4 (1st October 2020) - Young, Megan E.; Demers, Lindsay B.; Parker, Victoria; Day, Hollis; Chao, Serena
ABSTRACT: Internal medicine residency programs consider effectively discharging patients from the hospital an important training milestone. However, it is rare for residents to have the opportunity to follow discharged patients into the community and see discharge plans in action. This curriculum provided residents with the opportunity to evaluate patients in their homes after they were discharged from the hospital to assess the alignment of the discharge plan with patients' real-life circumstances. Thirty-nine internal medicine residents participated in a structured exercise during a posthospital discharge home visit to older patients they cared for during the hospital admission. After completing the exercise, residents were asked what they learned from the experience. We found that by visiting patients' homes, residents were able to better assess patient needs, which highlighted the necessity for more individualized discharge plans with regard to in-home functioning, communication with caregivers, and medication reconciliation. Further, the posthospital visit exercise enhanced residents' awareness of challenges in developing and implementing discharge care plans for complex older patients.